When fair is not equal: compassion and politeness predict allocations of wealth under different norms of equity and need - Zhao, Kun; Ferguson, Eamonn; Smillie, Luke D. (SAGE, 2017)
Growing evidence has highlighted the importance of social norms in promoting prosocial behaviors in economic games. Specifically, individual differences in norm adherence—captured by the politeness aspect of Big Five agreeableness—has been found to predict fair allocations of wealth to one’s partner in the dictator game. Yet most studies have used neutrally-framed paradigms, where players may default to norms of equality in the absence of contextual cues. In this study (N = 707), we examined prosocial personality traits and dictator allocations under salient real-world norms of equity and need. Extending on previous research, we found that—in addition to politeness—the compassion aspect of agreeableness predicted greater allocations of wealth when they were embedded in real-world norms. These results represent an important step in understanding the real-world implications of laboratory-based research, demonstrating the importance of both normative context and prosocial traits.